An integrative literature review: design and stages of peace group counselling as peace counselor/educator strategies for fostering a peace mindset - Supriyanto, Agus; Wibowo, Mungin Eddy; Mulawarman, Mulawarman; Japar, Muhammad (Intelektual Pustaka Media Utama, 2024)
Counsellors as peace educators are to foster a peaceful mindset to students. However, not every peace counsellor shares peaceful thinking with clients or students with problems as a gap. Peace group leaders can integrate counselling as a science with religion through the design and stages of peace group counselling (PGC). This research aims to design and organize PGC stages to facilitate peaceful thinking patterns in peace counsellors/educators (PC/E) to foster peaceful thinking patterns. Integrative literature review as a research model by collecting data through documentation with relevant books and journals, then analyzing it descriptively and qualitatively. The research findings found that the PC/E's duties as imams (group leaders) and kaffah individuals have therapeutic abilities. PC/E combines peaceful thinking with help from God. The PGC process has three stages: initial, work, and the final. The work stages combine the sub-stages of peace counselling, starting from rational, exploring the root causes of peaceful thoughts, self-reflection, seeking, and searching for peaceful thought patterns, looking for different forms and behaviors of peaceful thought patterns towards God's teachings as a novelty, and ending with evaluation and follow-up. PC/E implements the PGC design and stages so that individuals can cultivate a peaceful mindset through training and experimental research.